LECTURER’S FEEDBACK ON ESSAY WRITING IN HIGHER EDUCATION - Dini Irawati; Mohammad Ilyas (Sekolah Tinggi Pariwisata Mataram, 2022)
Writing is one of English skills that is considered as a productive skill which means a skill that can produce some things, such as ideas, thoughts, and expressions in written form. On intermediate students, the kind of writing taught in the class was essay writing. An essay writing is a series of paragraphs written on a single topic with a single main idea. In the practice of writing essay, students need proper feedback to be given in the process of writing to improve their writing skills, especially from the lecturer. Lecturer holds a significant role in assisting students developing their writing. The types of lecturer’s feedback are the written-oral feedback, the direct-indirect feedback, the form-content feedback, and the first-final draft feedback. This research is aimed to know what types of feedback used by the lecturer in students essay writing work of fourth semester students of English Education Department of UINSI Samarinda in academic year 2020/2021. The research used the qualitative approach and the descriptive design. The data analysis technique used in this research was following the model of data analysis from Miles, Huberman, and Saldana , namely (1) data condensation, (2) data display, and (3) conclusion drawing/verification. The result showed that there were four types of feedback found in this research, namely written-oral feedback, direct-indirect feedback, form-content feedback, and first-final draft feedback.